Sharia Economic Law Analysis of Foreign Currency Buying and Selling In Forex Trading Transaction at PT. Didimax Berjangka - Luthfiah, Siti Endri; Al-Hakim, Sofian; Susilawati, Cucu (Fakultas Syariah IAIN Kerinci, 2024)
This research aims to determine the law of buying and selling currency in forex trading transactions at PT. Didimax Futures. Forex trading is a currency transaction from various countries involving major money markets and brokers and is carried out 24 hours a day. PT. Didimax Berjangka is the leading and first broker company in Indonesia. This research uses a qualitative approach with descriptive methods. The research results found that money cannot be used as a trading commodity, according to Al-Ghazali's opinion in the Book of Ihya Al-Ulumudin. However, based on the DSN-MUI fatwa Number 96/DSN-MUI/IV/2015 concerning Hedging Transactions, forex trading transactions are permitted because, in the fatwa, the laws of trading and forex are equated using mutual promises (muwa'addah). According to the author's analysis, forex trading transactions carried out by PT. Didimax is by the DSN-MUI fatwa because it uses a promise agreement (wa'ad) when carrying out transactions. In conclusion, it buys and sells currency in forex trading transactions at PT. Didimax Berjangka is permitted according to Sharia Economic Law.